Polymer gel-based measurements of the isocenter accuracy in an MR-LINAC. (August 2019) - Dorsch, S; Mann, P; Elter, A; Runz, A; Klüter, S; Karger, C P
Abstract: As magnetic resonance-guided radiotherapy (MRgRT) is becoming increasingly important in clinical applications, the development of new quality assurance (QA) methods is needed. One important aspect is the alignment of the radiation and imaging isocenter. MR-visible polymer gels offer a way to perform such measurements online and additionally may allow for 3-dimensional (3D) evaluation. We present a star shot measurement irradiated and scanned with a 0.35 T MR-LINAC device evaluating the polyacrylamide gelatin (PAGAT) gel dosimeter immediately and 48 h after irradiation. The gel was additionally scanned at a 3 T MR device 5 h and 52 h after irradiation. The evaluation revealed an isocircle radius of 0.5 mm for both imaging devices and all image resolutions and time points after irradiation. The distance between radiation and imaging isocenter varied between 0.25 mm and 1.30 mm depending on the applied image resolution. This demonstrates that evaluation of a star shot measurement in a 0.35 T MR-LINAC is feasible, even immediately after irradiation.